2013
DOI: 10.1080/02687038.2013.803515
|View full text |Cite
|
Sign up to set email alerts
|

The actual and potential use of gestures for communication in aphasia

Abstract: Background: Two main conflicting positions exist concerning the relationship of gesture and speech. The first claims that gesture and speech constitute a single bimodal production process that leads to an impairment of both communication channels in the case of aphasia. The second accounts for two independent but tightly coordinated processes with a trade-off relationship of gesture and speech. According to the latter assumption, speakers who have aphasia should be able to compensate for their verbal deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 69 publications
6
69
0
1
Order By: Relevance
“…In the first of these studies by Hogrefe et al . (), 24 participants with aphasia were required to retell short film clips under two conditions. In the first, ‘verbal’ condition, participants were instructed to retell the story using speech.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first of these studies by Hogrefe et al . (), 24 participants with aphasia were required to retell short film clips under two conditions. In the first, ‘verbal’ condition, participants were instructed to retell the story using speech.…”
Section: Introductionmentioning
confidence: 99%
“…In both studies (Hogrefe et al . , Mol et al . ), the metric used for scoring gesture informativeness was a forced choice: Was this the sweater scenario or the accident scenario, or which of the set of six videos was being narrated.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the employment of gestures among individuals with aphasia, Hogrefe, Ziegler, Weidinger, and Goldenberg (2012) have also recently reported that speakers with severe aphasia tended to employ gestures more as a strategy to convey messages using an alternative means of communication. A follow-up study by Hogrefe, Ziegler, Wiesmayer, Weidinger, and Goldenberg (2013) revealed that some speakers with aphasia used gestures spontaneously to compensate for their limited verbal output and, more interestingly, these co-verbal gestures conveyed more information than the corresponding spoken expression. Parallel to Le May’s (1988) findings of significantly more kinetographs used by speakers with aphasia, Herrmann, Reichle, Lucius-Hoene, Wallesch, and Johannsen-Horbach (1988) reported that speakers with aphasia gestured significantly more frequently and for a significantly longer period of time than their normal conversational partners.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Palmer et al (2012) argued that the advances in artificial intelligence and audiovisual signal processing make it possible to automate certain SLT tasks and thus deliver more intensive and efficient therapy out of the clinics, while making better use of the therapists' time. The state-of-the-art in this area includes web-based developments (Ooi, Raja, Sung, Fung, & Koh, 2012), mobile applications (Bunnell & Beidel, 2013) and various types of robots (Choe, Jung, Baird, & Grupen, 2013;Kose, Akalin, & Uluer, 2014), featuring components of voice-based and gesture-based interaction (Hogrefe, Ziegler, Wiesmayer, Weidinger, & Goldenberg, 2013;Sekine & Rose, 2013), avatars in the role of 'virtual therapists' (Abad et al, 2013;Teodoro, Martin, Keshner, Shi, & Rudnicky, 2013), etc. Expert systems have been used in this area, for example, to adapt parameters of the user interfaces, in order to make them more amenable and engaging (Kostoulas et al, 2012).…”
Section: Therapy Enforcementmentioning
confidence: 99%